High precision survey and alignment of large linear accelerators - Prenting, J; Schlösser, M; Herty, A; Green, J; Grzelak, G; Mitra, A; Reichold, A (Joint Accelerator Conferences Website (JACoW), 2005)
Future linear accelerators require new survey techniques to achieve the necessary alignment precision. For TESLA, the demanded accuracy for the alignment of the components is 0.5mm horizontal and 0.2mm vertical, both on each 600m section. Other proposed linear colliders require similar accuracies. These demands can not be fulfilled with common, open-air geodetic methods, mainly because of refraction in the tunnel. Therefore the RTRS (Rapid Tunnel Reference Surveyor), a 25m long measurement train performing overlapping multipoint alignment on a regular tunnel reference network is being developed. Two refraction-free realizations of this concept are being developed at the moment: GeLiS measures the horizontal co-ordinates using multipoint alignment with stretched wires as strightness reference. In areas of the tunnel where the accelerator is following the earth curvature GeLiS measures the vertical co-ordinate using a new hydrostatic levelling system (HLS). LiCAS is based on laser straightness monitors (LSM) combined with frequency scanning interferometry (FSI) in an evacuated system. LiCAS measures both coordinates with respect to its LSM-beam and thus is suitable for geometrically straight tunnel sections. Both measurement systems will be placed on a train, which could do the reference survey autonomous or semiautonomous.